Fundamental Factors, Economic Value Added, and Other Factors Determining Stock Return - Afifah Noviyanti; Friska Firnanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical evidence about the effect of operating cash flow, investing cash flow, financing cash flow, market to book ratio, earnings per share, price earnings ratio, economic value added and market value added on stock return. The population used in this research are non-financial companies listed in Indonesia Stock Exchange from 2018 to 2020. The sample used for this research consists of 143 listed non-financial companies. The sampling technique used purposive sampling method and analyzed using multiple regression method. The result of this research shows market to book ratio has positive effect toward stock return, add the other independent variables such as operating cash flow, investing cash flow, financing cash flow, earnings per share, price earnings ratio, economic value added and market value added have no effect toward stock return.